A German Approach to Freeway Facility Evaluation. Issue 1 (January 2015) - Hartmann, Martin; Vortisch, Peter; Schroeder, Bastian J.
In the Highway Capacity Manual 2010 (HCM 2010), Chapters 10 to 13 provide the methodology for analyzing freeway facilities in relation to level of service (LOS). Supplemental Chapter 25 contains additional details on the analytical methodology, which is tied to a computer program (FREEVAL) that implements the methodology and computer performance measures for oversaturated conditions. In the German Highway Capacity Manual (HBS), the methodology for oversaturated freeway facility analysis both assigns the complete facility with LOS F once the volume-to-capacity ratio on any of the component segments reaches 1.0 and terminates the analysis without further examination of the oversaturated segments. In German analysis practice, an alternative analysis should be performed next and represented, for example, by microscopic traffic flow simulation. But in practice, such simulation analyses are not often performed because of the complexity in the case of large freeway facilities. Therefore, a macro-scopic model able to handle the oversaturated traffic conditions is required. The FREEVAL implementation of HCM was tested for its usage in Germany but proved to be excessively U.S. specific and not applicable in Germany. The characteristics of the German facilities differ from those of the U.S. ones in driver behavior, capacity, and regulations and design standards. Therefore, a new approach was created to comply with German freeway design and operating standards, informed by lessons learned from the U.S. methodology. This paper presents the most important aspects of the German approach to freeway facility analysis and a direct comparison with implementation of the HCM software.